What Systematic Reviews Exist for the Effectiveness of Orthopaedic Interventions. (February 2019) - Wright, James G.; Davies, Jacqueline; Barwick, Melanie A.; Hawker, Gillian A.; Prieto-Alhambra, Daniel; Coyte, Peter C.
Abstract : Introduction: Orthopaedics procedures are frequent and expensive, but highly cost effective in improving the quality of life. The purpose of this study was to determine the number and topics of systematic overviews on the effectiveness of orthopaedic interventions. Methods: We performed a review of PubMed, Ovid Embase, Scopus, OrthoEvidence, and the Cochrane Library for dates of publication from January 1, 2006, to February 3, 2017, to identify systematic overviews of randomized clinical trials for the effectiveness of therapeutic interventions involving orthopaedic surgeons. Abstracts were excluded based on the following sequentially applied criteria: (1) the systematic review did not include an intervention for an orthopaedic condition; the intervention was not therapeutic; the intervention was not likely to be applied or influenced by an orthopaedic surgeon; (2) the study was not a systematic review or the study was a single randomized controlled trial, and/or it included nonhuman studies; (3) the systematic review included nonrandomized studies; and (4) the systematic review did not state moderate or strong evidence in support of the study conclusion(s). Results: Of the 6, 864 abstracts found in the searches, 6, 145 were excluded yielding 719 systematic overviews. Contrary to conventional wisdom, this study identified 719 reviews of randomized controlled trials of therapeutic orthopaedic interventions. The interventions were classified as surgical in 383 (55%), medication in 245 (34%), and rehabilitation in 42 (6%), and other nonsurgical interventions in 39 (5%). Discussion: This study identified many systematic overviews of orthopaedic interventions. The findings of this study could both influence clinical practice and, given the frequency of orthopaedic procedures, have a major public health impact.